ANALISIS MOTIVASI DAN HASIL BELAJAR MAHASISWA PPKN UNIVERSITAS RIAU BERDASARKAN TINGKATAN UKT (UANG KULIAH TUNGGAL) - Khilda Rahmadani; Sri Erlinda; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by the researchers' curiosity about the motivation and learning achievement of students when based on tuition fees for each student. Where the authors find symptoms of differences in student learning motivation in terms of various indicators of learning motivation. With these differences in learning motivation, researchers also observe differences in learning achievement of students who follow them. Here the researcher will present the analysis of motivation and student learning achievement at tuition fee level I, II, III and tuition fee level IV. This research method is descriptive quantitative, data collection techniques used questionnaires, interviews and documentation. The research variable is learning motivation which consists of 6 indicators of 14 questions based on the research instrument. The population of this study were all active college students from 2016- 2019 grade. The sample of this study was taken using a quota sampling technique. The number of samples taken in this study were 80 people. Based on the results of research and recapitulation that has been done by researchers. Based on the motivation data and learning achievement, it can be seen that students with tuition fee level I, II and tuition fee level IV have a level of motivation to learn “High